Psikologi Moral Penonton Film Serial Layangan Putus - Kelen, Konradus Doni; Kami, Kanisius; Kamuri, Paulus Ama; Nusa, Silverter; Malo, Ariyanti (Ideas Publishing, 2025)
This study started from curiosity about the serial film Layangan Putuh which attracted a lot of attention from Indonesian people in all circles. The purpose of this study was to find out the responses of the viewers of the serial film Layangan Putuh and analyze it with the theory of literary psychology. The method used in this study was qualitative with the technique of obtaining information through in-depth interviews with students at Weetebula Catholic University. The results of this study indicate that most of the students reject the cheating behavior played by the characters Aris and Lydia. They see it as a disgrace. The data for this study were obtained from in-depth interviews. The results of this study can be used as evaluation and control material for families to maintain loyalty in family life